2008
DOI: 10.3844/ajabssp.2008.330.336
|View full text |Cite
|
Sign up to set email alerts
|

Specific Heat and Thermal Conductivity of Berberis Fruit (Berberis vulgaris)

Abstract: Abstract:Berberis fruit was known as a medicinal and ornamental plant in the world. It is used in medicine to cure the liver, neck and stomach cancer, blood purification and mouth scent. In order to design of equipments and facilities for the drying, preservation and processing of berberis, it is necessary to know about the specific heat and thermal conductivity. Therefore, the objectives of this study were to determine the specific heat and thermal conductivity of berberis as well as to develop mathematical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Berberis species are mainly consumed fresh, dried and used in juice production [4]. The fruits are very popular, known as zereshk in Iran where they are commonly used for cooking and in jam production, thus, encouraging the production of fresh edible seedless barberries fruits reaching about 22,000 tons per annum [5]. The fruits are also processed into beverages, drinks, syrups, candy and other confectionary products which are popular Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Berberis species are mainly consumed fresh, dried and used in juice production [4]. The fruits are very popular, known as zereshk in Iran where they are commonly used for cooking and in jam production, thus, encouraging the production of fresh edible seedless barberries fruits reaching about 22,000 tons per annum [5]. The fruits are also processed into beverages, drinks, syrups, candy and other confectionary products which are popular Iran.…”
Section: Introductionmentioning
confidence: 99%
“…where, T is temperature (C), t is time (s), ρ is thermal resistivity (C/W) and r is radial distance (m). The solution to Equation (1) is (Aghbashlo et al, 2008;Opoku et al, 2006):…”
Section: Theorymentioning
confidence: 99%
“…Moisture content and temperature levels are considered according to previous studies which were carried out for fruits with initial moisture content of more than 80% (w.b.) (Aghbashlo 2008). Bulk density is defined as mass per unit of volume of material.…”
Section: Methodsmentioning
confidence: 99%
“…The results of experiments indicated that the specific heat of barberry varied within the range of 1.9653 to 3.2911 kJ/kg °C. The variation range of thermal conductivity coefficient was 0.1324 to 0.4898 kJ/ kg °C (Aghbashlo et al 2008).…”
mentioning
confidence: 99%